The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0218960
|View full text |Cite
|
Sign up to set email alerts
|

Preconception nutrition intervention improved birth length and reduced stunting and wasting in newborns in South Asia: The Women First Randomized Controlled Trial

Abstract: South Asia has >50% of the global burden of low birth weight (LBW). The objective was to determine the extent to which maternal nutrition interventions commenced before conception or in the 1 st trimester improved fetal growth in this region. This was a secondary analysis of combined newborn anthropometric data for the South Asian sites (India and Pakistan) in the Women First Preconception Maternal Nutrition Trial. Participants were 972 newborn of mothers who were poor, rural, unselected on basis of nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 45 publications
0
21
0
2
Order By: Relevance
“…In this study, more than 50% of women of childbearing age had a low socioeconomic status, meaning they were living in poverty, which challenges well-being, as demonstrated, for example, in studies on women of rural communities in south Asian countries [ 4 ]. Living in poverty increases the risk for food insecurity and consuming cheap foods with a low density of essential nutrients promotes micronutrient deficiencies (or hidden hunger) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, more than 50% of women of childbearing age had a low socioeconomic status, meaning they were living in poverty, which challenges well-being, as demonstrated, for example, in studies on women of rural communities in south Asian countries [ 4 ]. Living in poverty increases the risk for food insecurity and consuming cheap foods with a low density of essential nutrients promotes micronutrient deficiencies (or hidden hunger) [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutritional status at the time of oocyte implantation is a key determinant factor of embryonic and fetal growth [ 1 , 2 ]. Previous studies indicated that nutritional interventions prior to and during pregnancy can positively influence a newborn’s birthweight and well-being [ 3 , 4 , 5 ], making early dietary and lifestyle interventions a key strategy for achieving optimal population health. Obese women and their future children also benefit from interventions to achieve optimal weight before pregnancy, since obese childbearing-age women might have impaired fertility and increased risk for excessive weight gain during pregnancy, maternal complications, Cesarean delivery and fetal macrosomia, and ultimately higher mortality [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only two groups evaluated the impact of preconception supplementation in low-resource populations [ 33 , 34 ]. In the Women First Trial [ 34 , 35 ], a multicountry study done in the DR Congo, Guatemala, India, and Pakistan, fetal growth outcomes were improved if the supplement was provided before conception or late in the first trimester; the effect on maternal nutritional status has not been reported. In another Vietnam study, either a weekly multiple micronutrient supplement or a weekly iron/folate supplement were given to the women for at least 3 months prior to conception [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing stunting is part of the Sustainable Development Goals (SDGs) [1]. In many countries, interventions to reduce stunting have been carried out since the pregnancy period [2,3]. Poor maternal reproductive health and nutrition during pregnancy has lifelong impacts on the health of the offspring [4].…”
Section: Introductionmentioning
confidence: 99%